Futures in Old Testament Theology: Dialogic Engagement - Brueggemann, Walter (2015)
No one knows about the future of study in Old Testament theology. Two things seem clear. First, we are likely to be surprised by new emerging methods and perspectives, new critical judgments, and new interpretive extrapolations. If we think back to about 1990, Old Testament theology had reached what seemed to be dead end; and then in the next decade, to some great extent due to the influence of Brevard Childs, we witnessed a great revival of study in new directions. I anticipate that we might, at any time, witness the same sort of newness among us the shape of which we cannot foresee. Second, we are sure to continue rich diversity in method, perspective, critical judgment, and interpretive extrapolation, influenced as each of us is by social location, habit, conviction, and tradition. More than such surprise and such continuing diversity we cannot know.
Keywords: Old Testament Theology -- Biblical Theology -- narrative -- dialogic engagement